Anisotropic design and optimization of conformal gradient lattice structures. (February 2020) - Li, Dawei; Liao, Wenhe; Dai, Ning; Xie, Yi Min
Abstract: In this work, we present a novel anisotropic lattice structure design and multi-scale optimization method that can generate conformal gradient lattice structures (CGLS). The goal of optimization is to achieve gradient density, adaptive orientation and variable scale (or periodic) lattice structures with the highest mechanical stiffness. The asymptotic homogenization method is employed for the calculation of the mechanical properties of various lattice structures. And an equation of elastic tensor and relative density of the unit cell is established. The established function above is then considered in the numerical optimization schemes. In the post-processing, we propose a numerical projecting method based on Fourier transform, which can synthesize conformal gradient lattice structure without changing the size and shape of the unit cells. Besides, the algorithm allows us to minimize distortion and prevent defects in the final lattice and keep the lattice structures smooth and continuous. Finally, in comparison with different parameters and methods are performed to demonstrate the superiority of our proposed method. The results show that the optimized anisotropic conformal gradient lattice structures are much stiffer and exhibit better structural robustness and buckling resistance than the uniform and the directly mapped designs. Graphical abstract: Highlights: An anisotropic design and optimization method is proposed for conformal gradient lattice structures. The optimized lattice structures exhibit conformal gradient density, adaptive orientation, variable period. These anisotropic conformal lattice structures are much stiffer than uniform and directly mapped designs.